A developing country's commercial banking risk governance disclosures: Post‐financial crisis. (3rd November 2020) - Weekes‐Marshall, Diana
Abstract: Risk governance disclosures (RGDs) provide users with valuable information and greater corporate insights about the management, oversight and strategic direction of the organisation. However, insufficient research has been conducted in this area. RGDs reduce information asymmetry and increase transparency. This study examines the level of RGDs in the commercial banks (CBs) of a developing country where most RGDs are voluntary and made at management's discretion. The study adopted a quantitative, multi‐method approach. RGDs for two publicly listed CBs in Barbados were analysed over 10 years (2007–2016) using a risk governance disclosure index (RGDI). Correlations were also used to determine if a relationship existed between the disclosures and performance. Disclosures were found to be general and non‐standardized. Company‐specific disclosures were infrequent, and annual disclosures were repetitive and symbolic. No significant relationships were discovered between corporate governance disclosures and performance. However, but bank performance indicators were found to be positively related to risk disclosures. A limitation of the study is that only two of the six CBs reported in a manner suitable for this study. Hence, reducing the number of observations. This was overcome through the use of a longitudinal approach which allowed for improved understanding of RG reporting practices in this sector. The results provide valuable insights which supplement the existing literature. They also provide pertinent information for standard‐setters, regulators and preparers of the reports. The study contributes to the existing literature in that it examines the disclosure behaviours of CBs in a non‐traditional governance model in an economy with limited research.